Unidade de ensino potencialmente significativa para o ensino da divisão celular no ensino médio - Costa, Janine Araújo (2024)
This dissertation is based on the need to contribute to the teaching-learning process in Sciences, through a didactic proposal - Potentially Significant Teaching Unit (UEPS), aimed at promoting meaningful learning in high school students, on the theme ¿ Cell division¿. The study, at the same time as defending meaningful learning, is part of the issue relating to teaching Cell Division content, considering it a fundamental concept in the field of Biological Sciences, as it involves the reproduction, growth and regeneration of organisms. Understanding this process is essential for understanding a greater degree of complexity of various biological details and for understanding the basis of life at the cellular level. Given this, the study is guided by the following research question: What are the contributions of a UEPS to the teaching-learning process of Cell Division content in high school? Based on this question, the general objective is to develop, apply and analyze a UEPS focused on promoting meaningful learning in high school students in the Cellular Thematic Division. The teaching methodology adopted in the present study is based on an approach that proposes the structuring of a teaching unit to be developed in seven meetings, thirteen periods, in the Biology discipline in High School based on what was announced by Moreira (2011) for a UEPS taking aspects related to the Meaningful Learning Theory (TAS) as its main reference. In methodological terms, the research is linked to a qualitative approach and action research, analyzing signs of significant learning in the different activities carried out throughout the activities that characterized the UEPS. As instruments for data production, the study relies on the logbook filled out by the researcher who assumes the role of class teacher and on the materials produced by the students during the activities, especially the conceptual maps produced in the last meeting. As a result of the study and in response to the central question, the study points out that the way in which the UEPS was organized and the activities selected promoted signs of significant learning, with emphasis on activities that involve the recovery of prior knowledge, the approach to content starting from from more inclusive and general concepts to more specific ones and the activity aimed at evaluating the contributions of UEPS to learning, represented by concept maps. The maps analyzed in the study exemplify the expansion of knowledge from the beginning of UPES to its end, bringing more elements and ideas in a connective and hierarchical way. Added to this, the activity proved to be of interest to students, especially due to the use of digital technologies and manipulative activities, as well as demonstrating the didactic feasibility of applying the UEPS in the way it is organized in the study. The educational product that accompanies this dissertation refers to support material for the teacher, bringing the didactic sequence developed in the form of UEPS, and the materials and resources used. This educational product is available on the program page, as well as on the EduCapes portal (http://educapes.capes.gov.br/handle/capes/742679)